Consumers perception on green marketing towards eco-friendly fast moving consumer goods - K Pradeep Reddy; Venkateswarlu Chandu; Sambhana Srilakshmi; Elia Thagaram; Ch. Sahyaja; Bernard Osei (International Journal of Engineering Business Management, 2023)
In today’s commercial world, ecological concerns have become increasingly essential. A lot of governments care about environmental issues. Sustainable development that doesn’t harm the environment is a major concern for companies today. The term “green marketing” describes the strategy of promoting and selling goods and services because of their positive impact on the natural world. Either the product or service itself is environmentally friendly, or the manufacturing process, packaging, and marketing are modified to be more eco-friendly. Concerns about how products harm the environment have recently been expressed by both manufacturers and consumers. Lead-free paint, organic foods, and low-power (or “energy-efficient”) electrical equipment are examples of products that consumers and manufacturers are focusing on as being “green” or ecologically friendly. Additionally, the importance of the green marketing idea is becoming more and more apparent to marketers. Though numerous green marketing studies have been conducted globally, there hasn’t been much academic research on consumer perception and preferences in India. This study explores consumer green ideals, environmental knowledge, green behaviours, and green products in addition to providing a brief review of environmental challenges. This article emphasises consumer views of and favorites for green marketing tactics and goods through the use of a planned questionnaire. To study was lead on 702 respondents. Customers demonstrated a high level of knowledge about eco marketing tactics and products. The respondents also showed strong environmental values. Research has offered helpful insights for green product marketers owing to the great perceived eco cost amongst customers, and it emphasises essential for creating marketing communication campaigns promoting green products.